Postoperative adjuvant therapy following radical resection for intrahepatic cholangiocarcinoma: A multicenter retrospective study - Lei Wang; Manjun Deng; Qiao Ke; Jianying Lou; Shuguo Zheng; Xinyu Bi; Jianming Wang; Wei Guo; Fuyu Li; Jian Wang; Yamin Zheng; Jingdong Li; et al. (Cancer Medicine)
Abstract Background and Aims The prognosis of intrahepatic cholangiocarcinoma (ICC) after radical resection is far from satisfactory; however, the clinical value of adjuvant therapy (AT) remains controversial. This multicenter study aimed to evaluate the clinical value of AT and identify potential patients who would be benefited from AT. Methods Data from ICC patients who underwent radical resection were retrospectively collected from 12 hepatobiliary centers in China between December 2012 and December 2015. Patients were divided into AT and non‐AT groups based on whether AT was administered or not. Overall survival (OS) and disease‐free survival (DFS) were analyzed using the Kaplan‐Meier method before and after 1:2 propensity score matching (PSM). Subgroup analyses were conducted based on the established staging systems. Results A total of 412 patients were enrolled in this study, and 77 patients (18.9%) received AT, including 32 (7.8%) patients who received transarterial chemoembolization (TACE), 21 (5.1%) patients who received chemotherapy, 10 (2.4%) patients who received radiotherapy, and 14 (3.4%) patients who received adjuvant chemoradiotherapy. The median OS and DFS were both longer in the AT group than in the non‐AT group (43.0 months vs 21.0 months, P = .015; 16.0 months vs 11.0 months, P = .045, respectively), and the advantage of AT was confirmed for both the OS and DFS (P = .023; P = .046, respectively) after 1:2 PSM. Furthermore, based on the established nomogram, only “middle‐risk” patients receiving AT cherished a longer median OS (43.0 months vs 20.0 months, P = .033). In subgroup analyses that were stratified by different AT strategies, patients receiving postoperative chemotherapy had a longer median OS (37.0 months vs 21.0 months, P = .039), while patients receiving postoperative TACE had a longer median DFS (50.0 months vs 11.0 months, P = .007). Conclusion With the current data, we conclude that AT benefits ICC patients following radical resection, especially those “middle‐risk” patients, as evaluated by the established nomogram. However, exactly which patients are the most suitable for AT requires further study and validation.